Exergoeconomic analysis of a solar photovoltaic system in. Istanbul, Turkey - Izgi, Ercan; Akkaya, Yunus Emre (Tubitak Scientific & Technological Research Council Turkey, 2013)
This paper deals with the exergoeconomic analysis of a 750-Wp solar photovoltaic (PV) system that is constructed at the Meteorology Park of. Istanbul Technical University (41.102 degrees N, 29.02 degrees E) in. Istanbul, Turkey. It is known that seasonal differences cause a variation in the exergoeconomic parameters (energy and exergy loss rates) of solar PV systems. Due to this perspective, for regional climatic parameters 2 months are selected: April to represent the spring and August to represent the summer. Within this research, first the exergy analysis is performed on the system and then the economic values of the results are evaluated using the exergy, cost, energy, and mass (EXCEM) method. The energy efficiency of the considered system in August and April varies between 4.5% and 7.3% and 5.5% and 8.5%, respectively. Additionally, the exergy efficiency of the system in August and April varies between 3% and 5.3% and 3.8% and 6.5%, respectively. The average unit cost of the exergy values for August and April are calculated based on the EXCEM model as 0.214 W/$ and 0.129 W/$. Moreover, the average unit cost of the energy values for August and April are estimated as 0.222 W/$ and 0.134 W/$, respectively.
Keywords: Photovoltaic system; solar energy; exergy; exergoeconomic; solar irradiation; PLANTS; Computer Science; Engineering